DEVELOPMENT OF A WEB-BASED DIGITAL LIBRARY APPLICATION USING PHP AND MYSQL: A CASE STUDY IN CISARUA VILLAGE, SUKABUMI CITY - Dianamira, Lara; M.Kom, Ridwan,; Wahyudin Suganda, Munandar; Damuri, Amat (LPPM AMIK CBI Sukabumi, 2025)
In the current digital era, libraries no longer function merely as physical repositories for books; they have evolved into information centers that can be accessed online (Sulistyo-Basuki, 2003). Nevertheless, many local libraries still underutilize technology in managing their services and collections (Lasa, 2017). One such example is the Cisarua Village Library in Sukabumi City, which continues to rely on a manual system for book borrowing, returning, and reporting processes. Based on preliminary observations, this manual system has led to several operational challenges, including data recording errors, delays in report preparation, and discrepancies between system records and the actual physical condition of the collection (Kurniawan & Setiawan, 2019). To address these issues, a web-based digital library application was developed using PHP programming language and MySQL database (Pramudya & Kusrini, 2018). The application was built following the Software Development Life Cycle (SDLC) Waterfall model, encompassing stages such as requirement analysis, system design, implementation, testing, and deployment (Pressman, 2019). The main features of the application include: Admin and member login Book collection management (add, edit, delete), Book borrowing and return process, Daily, weekly, and monthly transaction reports, Book title search functionality, PDF file download (if available), Regarding database design, the table structure has.